Clinical profile of endometrial histopathological patterns in Abnormal Uterine Bleeding - Chauhan, Sapna; Radhakrishnan, Krishnapriya (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aims: To study the association of clinical profile of patients with Abnormal Uterine Bleeding with the different endometrial histopathological patternsMethods: A retrospective cross-sectional study was done in the department of Obstetrics and Gynaecology at a hospital in Karnataka, India from January 2017 to January 2019. Medical records were reviewed for all the cases of abnormal uterine bleeding who underwent endometrial biopsy.Results: There were 148 records of endometrial biopsies; >55% were in 41-50 years age group; 28% had postmenopausal bleeding; and 28% presented with menorrhagia. Menorrhagia and menometrorrhagia were equally common under 50 years of age. The various physiological patterns of endometrium (proliferative, secretory & menstruating endometrium) were noted in more than half the cases (51%). Proliferative endometrium was in 37%, followed by hyperplasia without atypia in 22% and only 3% showed malignancy; all of whom were in the postmenopausal group. Even in women with post menopausal bleeding, proliferative pattern was the commonest (33%), followed by atrophic endometrium and malignancy. Atypical hyperplasia was found to be most commonly associated with post menopausal bleeding.Conclusions: Both physiological and non physiological endometrial patterns were seen almost equally among the AUB cases. The knowledge of endometrial pattern in a case of AUB helps to decide a plan of management. Endometrial sampling plays a very important role in management of AUB, especially in the age group of more than 40 yrs; i.e, the peri and post-menopausal age groups, where incidence of malignant or pre malignant conditions was noted to be the highest.Key words: abnormal uterine bleeding, endometrial cancer, endometrial sampling, hyperplasia